SOME CALCULATED RESULTS OF TIDAL CURRENT SYSTEM BY USING THREE DIMENTIONAL MODEL (3D) IN THE GULF OF TONKIN - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2007)
This paper presents some characteristics of tidal current system which were calculated by using three dimensional model in the gulf of Tonkin. Calculated results of tidal current system were proved that: - During the flood time maximum velocity of the tidal current can reach to 53 cm/s. - During the ebb time maximum velocity of the tidal current can reach to 65 cm/s. General tendency of tidal current patterns is as follows: Propagation of tidal current into and out to of the gulf often started from the eastern part (Hai Nam coast)  and finished at the western part (Quang Binh) of the mouth. Areas of strongest tidal current distributed along the Hai Nam and Quynh Chau coasts during the flood and ebb times and Quang Ninh coast during the ebb phase. Calculated results by using three dimensional model have been shown that there are clearly changes in the intensity and direction between surface, middle and bottom layers of tidal current in the places where have the complicated topography